Extensive genome-wide duplications in the eastern oyster (Crassostrea virginica). (24th May 2021) - Modak, Tejashree H.; Literman, Robert; Puritz, Jonathan B.; Johnson, Kevin M.; Roberts, Erin M.; Proestou, Dina; Guo, Ximing; Gomez-Chiarri, Marta; Schwartz, Rachel S.
Abstract : Genomic structural variation is an important source of genetic and phenotypic diversity, playing a critical role in evolution. The recent availability of a high-quality reference genome for the eastern oyster, Crassostrea virginica, and whole-genome sequence data of samples from across the species range in the USA, provides an opportunity to explore structural variation across the genome of this species. Our analysis shows significantly greater individual-level duplications of regions across the genome than that of most model vertebrate species. Duplications are widespread across all ten chromosomes with variation in frequency per chromosome. The eastern oyster shows a large interindividual variation in duplications as well as particular chromosomal regions with a higher density of duplications. A high percentage of duplications seen in C. virginica lie completely within genes and exons, suggesting the potential for impacts on gene function. These results support the hypothesis that structural changes may play a significant role in standing genetic variation in C. virginica, and potentially have a role in their adaptive and evolutionary success. Altogether, these results suggest that copy number variation plays an important role in the genomic variation of C. virginica . This article is part of the Theo Murphy meeting issue 'Molluscan genomics: broad insights and future directions for a neglected phylum'.